The Impact of Changes in the Electronic Traffic Law Enforcement Organizational Structure on the Increasingly Complex Responsiveness of Traffic : JEL Classification: H83, K42, O33, R41, D73 - Irfan B; Mohamad Thahir Haning; Hasniati Hasniati; Nurdin Nara (Newinera Publisher, 2026)
This study examines public service innovation through the implementation of Electronic Traffic Law Enforcement (ETLE) in Makassar City, with a particular focus on organizational and structural transformation within the police institution. The research aims to analyze how ETLE, as a technology-based innovation, reshapes service delivery, institutional arrangements, and governance mechanisms in traffic law enforcement. Using a qualitative research approach, data were collected through in-depth interviews, direct observation, and document analysis involving key stakeholders within the Makassar City Police Traffic Unit and the South Sulawesi Regional Police Traffic Directorate. The analysis is framed using the Types of Local Public Innovation framework proposed by Queyroi et al. (2022), complemented by institutional and management innovation perspectives. The findings indicate that ETLE implementation has driven significant structural innovation, characterized by the addition of functional roles without expanding personnel, the establishment of a dedicated back office as the core of digital verification, and a clearer division of labor between front office and back-office units. These changes have enhanced transparency, accountability, and operational efficiency by shifting law enforcement practices from discretionary, face-to-face interactions to standardized, evidence-based digital processes. However, the study also identifies persistent challenges, including ineffective public notification mechanisms, limited cross-agency integration, and unresolved incentive governance for personnel. Overall, the research concludes that while ETLE demonstrates strong potential as a public service innovation, its long-term sustainability depends on strengthening institutional integration, incentive structures, and governance alignment alongside technological advancement.